Characterization of Liquefaction Products from Lignocellulosic and Aquatic Biomass - Telma Moreira; Maria Margarida Mateus; Luís C. Duarte; Maria Joana Neiva Correia (Biomass)
Biomass liquefaction is a promising thermochemical route to convert lignocellulosic residues into bio-oil. This study evaluates the liquefaction behavior of 13 biomasses with varying particle sizes (0.3–2.0 mm) and moisture contents (5–11%) under mild solvolysis conditions. High-performance liquid chromatography (HPLC-RID) and thermogravimetric analysis (TGA) were used to characterize bio-oil composition and biomass properties, respectively. Maximum conversion (72%) was achieved for Miscanthus, while Ulva lactuca reached only 23% due to its low carbohydrate content. Hemicellulose-rich feedstocks showed higher yields, whereas high lignin content generally reduced conversion. Furfural was the main compound identified in the aqueous phase (up to 51 g/L), reflecting extensive pentose degradation. Laboratory and industrial-scale liquefaction of cork and eucalyptus revealed scale-dependent differences. Industrial cork bio-oil showed increased xylose (0.70 g/L) and furfural (0.40 g/L), while industrial eucalyptus exhibited elevated levels of acetic (0.46 g/L) and formic acids (0.71 g/L), indicating enhanced deacetylation and demethoxylation reactions. These findings offer valuable insights for optimizing feedstock selection and process conditions in biomass liquefaction. The valorization of lignocellulosic residues into bio-oil contributes to the development of scalable, low-carbon technologies aligned with circular economy principles and bio-based industrial strategies.